Viver, aprender e trabalhar: habitus e socialização de crianças em uma comunidade de pescadores da Amazônia - CARDOSO, Luís Fernando Cardoso e (Universidade Federal do Pará, 2017)
The article analyzes Matá, a rural community of the lower Amazon approximately 55 km from the town of Óbidos. Using an ethnographic approach to daily life, the article focuses especially on families involved in fishing activities and the nature of children’s participation. Using Pierre Bourdieu’s concept of habitus, the analysis suggests that the activities undertaken by children in the community are not demeaning or exploitative, such as typically associated with the idea of child labor. Rather the inclusion of children in adult work acts as a strategy of socialization and self-reproduction essential for strengthening family ties, constructing distinctions between adulthood and childhood, and learning about the ecosystems of their environment.